Implementasi Nilai-Nilai Kebangsaan Bersumber Pancasila dan Bhineka Tunggal Ika Dalam Meningkatkan Kesadaran Keamanan Masyarakat: Studi Kasus Indonesia - Aziz, Rafi Nur; Soesanto, Edy; Taopik, Tandi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
One of the key tactics for cultivating attitudes and behavior based on Pancasila’s wishes in Indonesia is by applying Pancasil’s values which are considered to be the basis of Indonesian ideology and philosophy in raising public security awareness. It is unfortunate if, due to a lack of understanding and appreciation of the meaning of Pancasila, the principles that inspire and unite the people to fight for freedom and freedom become merely speechless and not fully united in everyday life. There are several ways to implement Pancasila’s values, one of which is through education, media, institutional development, cultural development, and economic development. Applications in education can be found in all subjects, in building school environments, and in exemplary behavior. Meanwhile, the principles of life that should be lived on the basis of Pancasila, such as inter-ethnic royalty, tolerance, agitation, contemplation, etc., can be taught in the villages of Pancaila. The integration of the ideals of Pancasila into public security awareness campaigns facilitates the understanding and practical application of the values of pancasila by the Indonesian community, thereby encouraging the formation of attitudes and behaviors that are oriented towards Pancasilla. In this respect, Indonesia has a visionary and firm moral foundation in its national policy.